Frequency of Rectal Cancer among Young and Older patients - Ashfaque A. Bhurgri, S. N, Khatti, A. A, Danish, M. Shaikh, N. Lal Seerani, A. Salam Memon, M. Khalid Shaikh, S. Raza, S. Z. Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of rectal cancer among young and older patients. Methods: All patients determined to have rectal carcinoma at tertiary consideration from January 2018 to December 2019 were recruited for this cross sectional study. Segment just as clinicopathological information of the rectal cancer patients were gathered reflectively and recently analyzed histologically affirmed instances of either sexual orientation remembered for this investigation while the patient critical ill and unstable patients, pregnant and lactating ladies and patient with hemorrhoids were rejected from the study. Patient information included age, sex, nationality, tumor morphology, tumor stage and separation, carcinoembryonic antigen (CEA) levels at show, and so forth. Results: Among all the fifty (50) patients under study, 30(60%) were below 40 years and 20(40%) were ≥40 yr of age. The mean age (yrs) at presentation was 46.64±8.74 the youngest patient was 18 years old. More than 70% of the patients were belonged to rural area of province including tribal and non-tribal population. Of the 50 patients, 45 were diagnosed with rectal adenocarcinoma, while five patients in the ≥40 yr age group had squamous cell carcinoma. The ulcerative morphology was identified as 20(40%) and 5(10%) in young and older patients whereas the polypoid morphology was seen in 10(20%) and 15(30%) young and older patients respectively. Among young and older population the level of tumour was also studied and observed as low 10(20%) and 12(24%) and high 8(16%) and 20(40%). In younger population the well, moderate and poorly differentiated cells was seen in 3(6%), 7(14%) and 6(12%) while in older patients the well, moderate and poorly differentiation was seen in 9(18%), 12(24%) and 13(26%). Conclusion: The young patients had transcendence of low rectal tumors, progressed T-stage and poorly differentiation tumor and advance level stage of illness stage when contrasted to older patients.